STRUCTURAL STEEL ANALYSIS DESIGN OF COMMERCIAL FACTORIES FOR LOADING AND EARTHQUAKE RESISTANCE - Sami N O Bakarman (NAROTAMA UNIVERSITY, Indonesia, 2019)
In the university my courses According to the widely used of